2012
DOI: 10.1371/journal.pone.0035347
|View full text |Cite
|
Sign up to set email alerts
|

BMP4 Was Associated with NSCL/P in an Asian Population

Abstract: BackgroundThe Bone Morphogenetic Protein 4 gene (BMP4) is located in chromosome 14q22-q23 which has shown evidence of linkage for isolated nonsyndromic cleft lip with or without cleft palate (NSCL/P) in a genome wide linkage analysis of human multiplex families. BMP4 has been shown to play crucial roles in lip and palatal development in animal models. Several candidate gene association analyses also supported its potential risk for NSCL/P, however, results across these association studies have been inconsisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
1
15
0
1
Order By: Relevance
“…A recent study reported that overexpression of the inhibitory Smad, Smad7, in neural crest cells repressed both TGFβ and BMP signaling, augmented apoptosis in branchial arches, and resulted in craniofacial anomalies [66]. Mutations in genes encoding a number of TGFβ superfamily members such as, TGFB3 [67], TGFBR1 ( ALK5 ) or TGFBR2 [68], ALK2/ACVR1 [69], ALK3/BMPR1A [70], BMP2 [71], BMP4 [72], BMP7 [73] and GDF11 [74] have been linked to CP formation. In the present study, genes encoding 40 members of the TGFβ superfamily (noted in “Results” and Table S1), were found to be differentially regulated subsequent to in utero AzaD exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that overexpression of the inhibitory Smad, Smad7, in neural crest cells repressed both TGFβ and BMP signaling, augmented apoptosis in branchial arches, and resulted in craniofacial anomalies [66]. Mutations in genes encoding a number of TGFβ superfamily members such as, TGFB3 [67], TGFBR1 ( ALK5 ) or TGFBR2 [68], ALK2/ACVR1 [69], ALK3/BMPR1A [70], BMP2 [71], BMP4 [72], BMP7 [73] and GDF11 [74] have been linked to CP formation. In the present study, genes encoding 40 members of the TGFβ superfamily (noted in “Results” and Table S1), were found to be differentially regulated subsequent to in utero AzaD exposure.…”
Section: Discussionmentioning
confidence: 99%
“…BMP4 is among the genes known to be functionally involved in craniofacial development. Building upon its biological function, as well as evidence from animal experimental studies [17] – [20] and human linkage studies [21] , [22] , BMP4 has been considered a leading candidate gene for NSCL/P and intensely studied in association studies using case-control [24] , [28] , [29] and case-parent trio designs [25] [27] . Four of the 9 published candidate gene studies provided supportive evidence for association between BMP4 and NSCL/P, where the identified SNPs included rs17563 [24] , [28] , [29] , rs10130587 [25] , rs762642 [26] and rs2855530 [27] .…”
Section: Discussionmentioning
confidence: 99%
“…122 single nucleotide variants (SNVs) in and around BMP4 were genotyped using the Illumina Human610-Quad v.1_B Bead Chip at the Center for Inherited Disease Research at the Johns Hopkins University of the US [8] . Based on the genomic structure of NM_130850.2 or NM_ 001202.3 for BMP4 ( http://genome.ucsc.edu/ ) [25] , these SNVs are located 3′ (n = 114), introns (intron_1 for rs762642 and intron_3 for rs2071047 ) and 5′ (n = 6) of the gene, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Chen et al [20] tested for possible association between markers in BMP4 gene and nonsyndromic CL±P in 297 Asian and Maryland trios. Their results does not support the evidence of linkage and association for the SNP rs17563.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, Chen et al [20] provided further evidence of association between BMP4 gene and nonsyndromic CL±P. They tested for possible association between markers in and around the BMP4 gene and nonsyndromic CL±P in Asian and Maryland trios.…”
Section: Introductionmentioning
confidence: 99%